STUDY OF THE INFLUENCE OF THE CONTRIBUTION OF FRAGMENTED RAMEAL WOOD AND MANURE ON THE DENSITY OF MICROSCOPIC FUNGI AND THE DENSITY OF MITES AND COLLEMBOLES OF A SANDY LOAM SOIL IN CONSTANTINE (ALGERIA) - Kerrouche, I; Bendjaballah, M; Abdelaziz, W; Bazri1, K. E. M; Behouhou, M. L; Ghdabna, R; Ouahrani, G (university of eloued -جامعة الوادي, 2022)
The objective of our work is to study the influence of the contribution of Fragmented Rameal Wood (BRF) and cattle manure on the density of microscopic fungi and the density of mites and springtails of a limono-sandy soil in Constantine (Algeria). A 100 m² parcel is subdivided into 15 plots of 2 m² each with 5 different plots where we determined the species of microscopic fungi and their density during March, April, May, June and November 2014. Thus, the density of springtails and mites was monitored monthly from March 2014 to January 2015
article
Keywords: Constantine; Fragmented Rameal Wood (BRF); Manure; microscopic fungi; mites; springtails